The novel N-rich hard carbon nanofiber as high-performance electrode materials for sodium-ion batteries. Issue 7 (1st April 2021) - Ma, Luxiang; Cao, Mengxiong; Zhao, Chun song; Huang, Shizhi; Ding, Jingyi; Chen, Jitao; Zhou, Yuan
Abstract: The low initial Coulomb efficiency and low specific capacity have always been the bottleneck restricting the development of carbon materials in the large-scale field of sodium ion batteries (SIBs) energy storage. Furthermore, the enormous biomass resources are not used reasonably and are burned or buried as garbage. Here we use a simple direct sintering method to transform the kitchen bio-waste into N-rich carbon nanofibers. Among them, the N-rich carbon nanofibers heated at 1300 °C deliver the best electrochemical performances in the cycling stability, rate capability and capacity retention, documented by the high capacity retention of 301 mAh g −1 at 0.1C rate after 100 cycles with initial coulomb efficiency of 80.0%. The design construct of building low-cost bio-waste carbon materials provides a new approach to develop high-performance anode materials for the SIBs and even other battery systems.